VILLAGE GOVERNMENT POLICIES IN RESOLVING LAND REGISTER CONFLICT - Antoni Antoni; Nitaria Angkasa; Lenny Nadriana (Green Publisher, 2023)
Land is a necessary area in socio-economic life. This study aims to determine the village government's policy in resolving land registration conflicts and village government policies in resolving land registration conflicts. The research is normative legal research using two approaches, namely the empirical juridical approach and the normative juridical approach. The results indicate that the village government's policy in resolving land registration conflicts is a village government policy submitted by the National Land Agency for land conflicts that have been granted usufructuary rights by the village government. The policies taken by the National Land Agency are not by the procedures and mechanisms stipulated in the Regulation of the Minister of Agrarian Affairs Number 9 of 1999, concerning procedures for the use of state land, as well as residents occupying land registers, were not used as an object in the formulation of policies and procedures for handling land registration conflicts. The village government is only a 3rd party, namely an intermediary. Procedures for handling land conflicts in the register include: submitting a complaint to the BPN, completing files, collecting authentic data, conducting the mediation, changing data, submitting old judges, and issuing legal co